Sie sind auf Seite 1von 6

z z¯ z

1

|z|

|z¯ w¯| = |z w|,

||z| − |w|| ≤ |z w|.

s Q

R\{0} → R,

t

t s

z |z| s f (z) = z/¯ |z| s

f

F : C C,

F (z) :=

f(z)

w z = 0

= 0

z

w C w F F C F F z k 0

w = F (0) =

k F(z k )

lim

z k C F (z k ) = f(z k ) F f |f (z)| = |z| 1s s > 1 s = 1 s < 1

s > 1 f (z k ) z k 0 z k = 1/k F (z k ) = f (1/k) = k s1 → ∞ F(z k ) w C s = 1 x k = 1/k y k = /k f (x k ) = 1 f (y k ) =

w = F (0) =

k F(x k ) = 1,

lim

w = F (0) =

k F(y k ) = .

lim

f s < 1 F (0) := 0 z k 0

k |F(z k )| = lim

lim

k→∞ |z k | 1s = 0.

R R t

F (0) := 0 f

t α α > 0 0

f N (z) :=

1

z +

N

n=1

2z

z 2 n 2 .

C\Z

z C\Z

¯

r > 0 B r (z) := {w C | |z w| ≤ r} C\Z f N | B r (z) f | B r (z) N 1 2(|z| + r) N 1 N > N 1

¯

¯

sup (z) |f(w) f N (w)| =

w

¯

B

r

sup

¯

wB r (z)

sup

¯

wB r (z)

n=N +1

n=N +1

w 2 n 2

2w

2w

((w 2 /n) 2 1)n 2

2(|z| + r)

1 (|z + r|/N 1 ) 2

n

2

n=N +1

1

3(|z| + r)

2

n=N +1

1

n

2

1 2 0 N → ∞

ζ(2) :=

f N | B r (z) f | B r (z) f z z f

n=1

n

¯

¯

2z

1

1

z 2 n 2 =

z + n + z n .

f N (z) =

1

z +

N

n=1

z + n + z n =

1

1

N

n=N

1

z + n

f N (z + 1) f N (z) =

N

n=N

1

1

1

1

z + n =

z + 1 + n

z + N + 1

z N .

z N → ∞ 0 f (z + 1) = f (z)

f(z) =

nZ

1

z + n

Z Z

Z = {0, 1, 1, 2, 2,

.} f N

f

sup

xR |f(x) f N (x)| ≤ sup

xR

n=N

|s n (x a n )| = sup

xR

n=N

|s n | =

n=N

|s n |.

n=1 |s n | 0 N → ∞ f N f

s n (x a n ) R\{a n }

f N R\{a 1 ,

f N | R\A

, a N } R\A f | R\A

x

f(a

+

n

) f(a n ) = s n = f(a n ) f(a )

n

f (a N ( ) > n

+

n

) f(a

|s n | <

2

n=N( )

n

) = 2s n > 0

δ

|x a n | < δ (x a i ) = (a n a i )

>

0

δ

<

|a n a i |

n

=

i

N ( )

f N (x) f N (a n ) =

N

k=1

s k ( (x a k ) (a n a k ))

= s n (x a n ) +

N

k=N( )

s k ( (x a k ) (a n a k ))

N N ( ) |x a n | < δ N ( )

N

k=N( )

s k ( (x a k ) (a n a k ))

2

k=N( )

|s k | <

 x ∈ (a n , a n + δ) ⇒ |f N (x) − f N (a n ) − s n | < x ∈ (a n − δ, a n ) ⇒ |f N (x) − f N (a n ) + s n | < N → ∞ x ∈ (a n , a n + δ) ⇒ |f(x) − f(a n ) − s n | ≤ x ∈ (a n − δ, a n ) ⇒ |f(x) − f(a n ) + s n | ≤

> 0

s n (x a n )

s n x n

f N (x) :=

N

n=1

s n (x a n )

f x y

f (x) =

f N (x) lim

lim

N

N

f N (y) = f(y).

h : 0, 1

2 R,

h(c) := f (c) f c +

1

2 .

= f( 2 ) + f (1) = h( 2 )

h h(0) h(0) 0 c [0, 1 2 ] h(c) = 0 f (c) = f (c + 1 2 )

f (0) = f (1) h(0) = f (0)

f ( 1 2 )

1

1

f : A Y x A

> 0 δ > 0 :

(y A) (d X (x, y) < δ)

d Y (f (x), f (y)) < .

f | A i f A i f | A i

x A f x > 0

, n} i x A i

I := {i 1 ,

f | A i k δ 1 ,

, i r } ⊂ {1,

, δ r > 0

(y A i k ) (d X (x, y) < δ k )

d Y (f (x), f (y)) <

k = 1,

, r δ := min 1kr δ k

r y k=1 A i k (d X (x, y) < δ )

d Y (f (x), f (y)) < .

J := I c := {1,

, n}\I i x A i

C :=

iJ

A i

x X\C x δ > 0 {y : d X (x, y) < δ } ∩ C =

(y A) (d X (x, y) < δ )

r y k=1 A i k (d X (x, y) < δ )

δ := min{δ , δ }

(y A) (d X (x, y) < δ)

f : R R,

d Y (f (x), f (y)) < .

f (x) :=

1

0

x 0 x < 0

A 1 := (−∞, 0) A 2 := [0, ) A := A 1 A 2 = R f | A 1 f | A 2 f 0

t [0, 1] {a n } ∈

{0, 1} N t =

n=1

a

n

2

n

φ

n=1

2a n

3

n

=

n=1

a

n

2

n

= t

φ x, y C

x :=

n=1

2a n

3 n ,

y :=

n=1

2b n

3 n .

x

a r < b r

= y r N a n

= b n

n < r a r

y x =

 ∞ ∞ 2(b n − a n ) = 2(b r − a r ) + 2(b n − a n ) 3 n 3 r 3 n n=1 n=r+1 2 ∞ 2 2 2 1 1 3 r − 3 n = 3 r − 3 r+1 · 1 − 2 = 3 r . n=r+1 3

= b r

a r > b r x y x y 3 r

|x y| ≥ 3 r ,

x < y a r < b r .

φ x, y C x < y a r < b r

φ(y) φ(x) =

 b n − a n = 1 ∞ b n − a n 2 n 2 r + 2 n n=r+1 ∞ 1 1 1 1 2 n = 2 r − 2 r+1 · 1 − 1 n=r+1 2

n=1

1

2 r

= 0

φ(x) φ(y) φ φ > 0 k N 2 k < δ = δ( ) = 3 k δ

|x y| < δ

⇒ |φ(x) φ(y)| ≤

x, y C |y x| < 3 k x < y x y r > k a r < b r

0 φ(y) φ(x)

1

2 r +

n=r+1

b r a r

1

2

r

2 k+1 +

n=k+2

1

n =

2

1

2

k

2 k < φ

[0, 1]\C x [0, 1]\C I = (a, b) x a, b C f I

φ(a) = lim f (x) = f (x) = lim f(x) = φ(b).

xa

xb

f f φ(a) = φ(b) > 0 φ y C φ(y) = φ(a) + φ b y

φ(a) φ(b) φ(y) = φ(a) +

> 0 φ(a) = φ(b)

f (x) := sup{φ(y) | y C, y x}.

φ φ(x) = f (x) x C f I = (a, b) [0, 1]\C a, b C I φ(a) φ(a) = φ(b) f > 0 k N 2 k < δ = δ( ) = 3 k

|x y| < δ

|f(x) f(y)| <

x < y |x y| < δ = 3 k x , y C (x, x ) C = = (y , y) C f (x) = φ(x ) f (y) = φ(y ) |x y | < 3 k φ

|f(x) f(y)| = |φ(x ) φ(y )| ≤ 2 k < .

f